Finite element modelling of bilayer iron powder compaction and evaluation on its relative density distribution using imaging technique - Mohd Yusoff, Syamimi (2022)
Multilayer compaction allows the manufacturing of advanced metal-based components ranging from long thin-walled sleeves to cutting tools. Combination of compressed powder layers has been proven to upgrade its mechanical properties in terms of its strength, durability and toughness compared to an individual layer. Following this, modern apparatus has applied layering principles to sustain the usage in daily life. Nevertheless, at the scale of research and development, inspection on unify powder layers are scant in the aspect of its internal density, particularly on its interconnected boundary layers or interface. This invites untimely defects of delamination and capping that would require unnecessary investment of time and effort during the secondary PM operation. All the while, the scope of density measurement has resorted to geometrical definition and hardness; thus, less modelling efforts had been undertaken to examine the sectioned powder layers. This study has developed an imaging technique and modelling procedures to assess the local relative density (or local RD) distribution on green single and bilayer iron ASC 100.29 powder compact. The modelling strategy was developed based on Finite Element Method (FEM) using Abaqus 6.20. The results of experimental distributed local RD values showed close agreement with values mentioned in the literature for green single layer powder compact and the current work was further improved with higher pixels. As expected, the modelled local RD values were validated for experimental local RD values green bilayer iron powder compact. Further, it was revealed that the highest local RD distribution on the interface of bilayer iron powder compact was obtained with H/D ratio of 1.6 under lubricated die condition. Besides, under all H/D ratios and low friction coefficient (μ of 0.08), smaller gradient of local RD distribution has been achieved by green bilayer iron powder compact compared to single layer iron powder compact with the same applied conditions.